2012
DOI: 10.1007/s00300-011-1151-6
|View full text |Cite
|
Sign up to set email alerts
|

Identifying gray whale (Eschrichtius robustus) foraging grounds along the Chukotka Peninsula, Russia, using satellite telemetry

Abstract: The purpose of this study was to evaluate summer and fall residency and habitat selection by gray whales, Eschrichtius robustus, together with the biomass of benthic amphipod prey on the coastal feeding grounds along the Chukotka Peninsula. Thirteen gray whales were instrumented with satellite transmitters in September 2006 near the Chukotka Peninsula, Russia. Nine transmitters provided positions from whales for up to 81 days. The whales travelled within 5 km of the Chukotka coast for most of the period they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…KDEs were calculated using the Kernel Density Analysis tool within ArcMap, with a search radius of 50 km and a cell size of 1 km, for each species with over 100 observations to display where each of the species were observed in this study (see Silverman 1986;Powell 2000). The 50 km search radius was used as a general daily displacement distance for cetaceans using foraging grounds (e.g., Hobbs et al 2005;Zerbini et al 2006;Dalla Rosa et al 2008;Heide-Jørgensen et al 2012;Kennedy et al 2014;Heide-Jørgensen et al 2015). The resulting KDEs were displayed using 10 quantiles.…”
Section: Data Analysesmentioning
confidence: 99%
“…KDEs were calculated using the Kernel Density Analysis tool within ArcMap, with a search radius of 50 km and a cell size of 1 km, for each species with over 100 observations to display where each of the species were observed in this study (see Silverman 1986;Powell 2000). The 50 km search radius was used as a general daily displacement distance for cetaceans using foraging grounds (e.g., Hobbs et al 2005;Zerbini et al 2006;Dalla Rosa et al 2008;Heide-Jørgensen et al 2012;Kennedy et al 2014;Heide-Jørgensen et al 2015). The resulting KDEs were displayed using 10 quantiles.…”
Section: Data Analysesmentioning
confidence: 99%
“…Even when shifts in shipping lanes are used, they may result in a reduction, but not elimination, of the risk of ship−whale encounters as whale aggregations may shift within and among years with shifts in prey or oceanographic conditions (e.g. Witteveen et al 2008, Chenoweth et al 2011, Becker et al 2012, Doniol-Valcroze et al 2012, Heide-Jørgensen et al 2012, Keller et al 2012, Pendleton et al 2012, Gregr et al 2013.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…Satellite-tags deployed on WNP individuals [29,30] and genetic and photo-ID comparisons between ENP and WNP individuals [31][32][33][34][35] demonstrated that at least a portion of the WNP whales migrated to Baja California. This indicated some degree of spatial overlap between the two populations, as ENP whales typically migrate from breeding grounds near Baja California to summer foraging areas in the Bering and Chukchi Seas [36][37][38][39]. However, genetic studies have consistently found significant differentiation, with some limited genetic exchange occurring [31,32,38,[40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%